2015
DOI: 10.1177/0098628315569877
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Programs That Maximize Psychology Major Success

Abstract: We conducted a national survey of psychology department chairs, and, based on their responses, we concluded that psychology programs differ in the number of students enrolled in various types of classes; the degree of focus on each of the goals recommended by the American Psychological Association (APA) Guidelines for an Undergraduate Psychology Education; the frequency of student participation in research, study abroad, and field placement; and the frequency of student-faculty interactions. We describe the pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
40
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 29 publications
(51 reference statements)
2
40
0
Order By: Relevance
“…Given the findings of many studies, such as Kuh et al (2017), which are on the importance of high-impact practices, and the results derived from the analysis of the NSSE data in the current study, it is thought that as institutions strive to increase student exposure to HIPS focusing on opportunities that meet the needs of adult learners (on campus or online) may not only increase overall student engagement but also benefit from resultant increases in student success measures, such as overall six-year graduation rates. Stoloff et al (2015) found that, although undergraduate admission tests are an indicator of student potential, programs including HIPS such as those detailed in this study can lead students to reach higher levels of student success, such as program completion and graduate school attendance. Thus, expanding the high-impact opportunities for all populations of students has the potential for meaningful gains in student success measures for institutions of higher education.…”
Section: Resultsmentioning
confidence: 68%
See 1 more Smart Citation
“…Given the findings of many studies, such as Kuh et al (2017), which are on the importance of high-impact practices, and the results derived from the analysis of the NSSE data in the current study, it is thought that as institutions strive to increase student exposure to HIPS focusing on opportunities that meet the needs of adult learners (on campus or online) may not only increase overall student engagement but also benefit from resultant increases in student success measures, such as overall six-year graduation rates. Stoloff et al (2015) found that, although undergraduate admission tests are an indicator of student potential, programs including HIPS such as those detailed in this study can lead students to reach higher levels of student success, such as program completion and graduate school attendance. Thus, expanding the high-impact opportunities for all populations of students has the potential for meaningful gains in student success measures for institutions of higher education.…”
Section: Resultsmentioning
confidence: 68%
“…In a national study based specifically on psychology majors, working with faculty members on research projects has been found to increase graduate school attendance (Stoloff, Good, Smith, & Brewster, 2015). Thus, it is important to increase student engagement in this high-impact practice, as the measures on Table 5 show that of the seniors surveyed only 40.5% of traditional and 27.4% of adult learners have participated or plan to participate in these student-faculty research projects.…”
mentioning
confidence: 99%
“…Our recommendation is to provide students with regular opportunities to engage in the statistical decision making process in the context of class research projects. It is widely recognized that scaffolded immersion in all aspects of the research process, from participation and/or data collection, through the development and testing of hypotheses, to the interpretation and reporting of findings, is a particularly effective way of teaching research skills (Bradstreet, 1996 ; Marek et al, 2004 ; Roberts and Allen, 2012 , 2013 ; Earley, 2014 ; Stoloff et al, 2015 ). This point was echoed by the academic participants in the current research, who reflected on how embedding statistical decision making in a context of substantive interest, and providing opportunities to work with personally meaningful data promotes student engagement.…”
Section: Discussionmentioning
confidence: 99%
“…This prominence reflects a widely held understanding that an ability to critically evaluate relevant research literature, the vast majority of which is quantitative (Kidd, 2002 ), is a necessary precursor to evidence-based practice (American Psychological Association Presidential Task Force on Evidence Based Practice, 2006 ). Engaging students regularly in all aspects of the research process is recognized as fundamental to teaching quantitative methods successfully (Bradstreet, 1996 ; Stoloff et al, 2015 ), hence the typical undergraduate psychology degree provides students with multiple opportunities to conduct empirical research, either individually or in collaboration with others (Perlman and McCann, 2005 ).…”
Section: Introductionmentioning
confidence: 99%
“…These areas largely match the American Psychological Association's (2014) five "pillars" of psychology that represent the core of the discipline: social/personality, mental and physical health, developmental, cognitive, and biological. However, psychology students generally have a great deal of flexibility in the courses that they must complete to graduate (Stoloff et al, 2010;Stoloff, Good, Smith, & Brewster, 2015). Many students have the option to take courses in niche areas of psychology, such as child psychopathology, drugs and behavior, and behavior modification.…”
mentioning
confidence: 99%